Perception of Teachers Regarding Gaps in Student Competencies for Industrial and Farmers’ Needs - Kaur, Manmeet; Anand, Anupam (Indian Journal of Extension Education, 2025)
This study was designed to describe the gap between the existing and desired competencies of the agricultural graduates as perceived by the teachers. A survey of active and continuously enrolled undergraduates and post-graduate students was conducted. Data for the study were collected by providing them with a questionnaire. The findings of the study revealed that the teachers’ perception of the competencies as existing and desired in the UG students was ordered in descending manner viz. communication/ICT, entrepreneurial, extension skills, personal, managerial, market/understanding government policy, and technical competency. While in the case of PG students, the teachers ordered the competencies as important in the desired status were communication/ICT, entrepreneurial, extension skills, managerial, personal, market/understanding government policy, and technical competency. The majority of the teachers agreed that the lack of staff was one of the major factors affecting their fair evaluation of the students along with the overburdening of various other universities works entrusted upon them. Recommendations include teachers should be assigned jobs concerning the schemes and mandates viz. teaching, research, and extension so that they can justify their scheme. The teachers in the teaching scheme should have the prime responsibility of building competencies among the students.